Comparative Study of facial Measurement between Bengali and Manipuri Adult Male Comparative Study of facial Measurement between Bengali and Manipuri Adult Male - Dutta, Kanta Sree; Chowdhury, Pratik; Ashrafuzzaman, Md; Khan, Md Habib; Nahar, Nurun (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: From the human face, we can identify their gender, age group, ethnicity etc. So facial morphometric study can be taken as part of anthropometric evaluation and it is an important parameter in observing inter population of faces among the same ethnic group or different group. If we can calculate the different craniofacial variables of different ethnic groups these can be used in future research or clinical purposes. To measure the facial variables among Bengali and Manipuri adult male and to compare these variables between two ethnic group. Methods and materials: A cross sectional, observational and analytic type of study was conducted on 200 sample which were collected by convenience sampling where 100 were Bengali adult male and remaining 100 from Munipuri adult male, aged between 18 to 50 years. Data for Bengali and Munipuri adult male were collected from Chattogram city and Kamolgonj, Sylhet respectively. The study was carried out in the Department of Anatomy, Chittagong Medical College from July 2016 to June 2017. Results: This study showed that mean morphological face height of Bengali and Manipuri were respectively 11.46 cm ± .53 and 11.82 cm ± .49, mean maximum facial breadth respectively13.04 cm ± .48 and 13.62 cm ± .45, mean facial index respectively 87.93 ± 2.58 and 86.89 ± 2.09. According to facial height, most common type in Bengali was low type (47%) and in Manipuri was medium type (39%). According to facial breadth most common type in Bengali was narrow type (63%) and in Manipuri was medium type (53%). Bengali have leptoprosopic (Narrow face) 53% followed by mesoprosopic face (Medium face) 43%. Manipuri have mesoprosopic face 59% followed by leptoprosopic type 31%. Conclusion: The results of the present anthropometric study on the adult Bangladeshi population can provide the basic framework for formulating standards of the facial dimension and indices for adult male of the Bengali and Manipuri population. JCMCTA 2021 ; 32 (2) : 122-127